Stereospecific capillary electrophoresis assays using pentapeptide substrates for the study of Aspergillus nidulans methionine sulfoxide reductase A and mutant enzymes. Issue 14 (8th June 2016) - Zhu, Qingfu; El‐Mergawy, Rabab G.; Zhou, Yuzhen; Chen, Chunyang; Heinemann, Stefan H.; Schönherr, Roland; Robaa, Dina; Sippl, Wolfgang; Scriba, Gerhard K. E.
Abstract : Stereospecific capillary electrophoresis‐based methods for the analysis of methionine sulfoxide [Met(O)]‐containing pentapeptides were developed in order to investigate the reduction of Met(O)‐containing peptide substrates by recombinant Aspergillus nidulans methionine sulfoxide reductase A (MsrA) as well as enzymes carrying mutations in position Glu99 and Asp134. The separation of the diastereomers of the N ‐acetylated, C ‐terminally 2, 4‐dinitrophenyl (Dnp)‐labeled pentapeptides ac‐Lys‐Phe‐Met(O)‐Lys‐Lys‐Dnp, ac‐Lys‐Asp‐Met(O)‐Asn‐Lys‐Dnp and ac‐Lys‐Asn‐Met(O)‐Asp‐Lys‐Dnp was achieved in 50 mM Tris‐HCl buffers containing sulfated β‐CD in fused‐silica capillaries, while the diastereomer separation of ac‐Lys‐Asp‐Met(O)‐Asp‐Lys‐Dnp was achieved by sulfated β‐CD‐mediated MEKC. The methods were validated with regard to range, linearity, accuracy, limits of detection and quantitation as well as precision. Subsequently, the substrates were incubated with wild‐type MsrA and three mutants in the presence of dithiothreitol as reductant. Wild‐type MsrA displayed the highest activity towards all substrates compared to the mutants. Substitution of Glu99 by Gln resulted in the mutant with the lowest activity towards all substrates except for ac‐Lys‐Asn‐Met(O)‐Asp‐Lys‐Dnp, while replacement Asn for Asp134 lead to a higher activity towards ac‐Lys‐Asp‐Met(O)‐Asn‐Lys‐Dnp compared with the Glu99 mutant. The mutant with Glu instead of Asp134 was the most active among the mutant enzymes. Molecular modeling indicated that the conserved Glu99 residue is buried in the Met‐ S ‐(O) groove, which might contribute to the correct placing of substrates and, consequently, to the catalytic activity of MsrA, while Asp134 did not form hydrogen bonds with the substrates but only within the enzyme.